A new species of Nemapalpus Macquart (Diptera, Psychodidae, Bruchomyiinae) from caverns in Minas Gerais State in southeastern Brazil - Bravo, Freddy; Barata, Ricardo Andrade (Zootaxa, 2012)
A new species of Nemapalpus Macquart collected in caverns in the state of Minas Gerais, southeastern Brazil, is described and named Nemapalpus spinosus sp. nov. A current list of the western hemisphere species of the genus is provided.